1987
DOI: 10.1007/bf00165038
|View full text |Cite
|
Sign up to set email alerts
|

PD 115,199: An antagonist ligand for adenosine A2 receptors

Abstract: PD 115,199, N-[2-(dimethylamino)ethyl]-N-methyl-4-(2,3,6,7-tetrahydro-2,6-dioxo-1,3- dipropyl-1H-purin-8-yl)benzenesulfonamide, was found to have high affinity for the A2 adenosine receptor labeled by 3H-NECA in rat striatal membranes (Ki 15.5 nM). Unlike other potent adenosine antagonists, which always showed some degree of selectivity for the A1 receptor, PD 115,199 had equal affinity at A1 and A2 receptors (Ki in 3H-CHA binding to A1 receptors 13.9 nM). 3H-PD 115,199 (126 Ci/mmol) was prepared by reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
2

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 9 publications
4
69
2
Order By: Relevance
“…The shift (4.1) in the concentration-response curve for R-PIA caused by DPCPX (2.5 nM) is consistent with a Ki value for the xanthine of about 0.8 nm, which is of the same order as the Ki value (0.54 nM) obtained for DPCPX in experiments recording nerve-evoked twitch responses from phrenic nerve-diaphragm preparations partially inhibited with tubocurarine and is also of the same order as the K, value for this xanthine at A1 adenosine receptors (Bruns et al, 1987;Lohse et al, 1987 (Hutchison et al, 1989) it seems likely that the excitatory effect of the adenosine analogues on [3H]-acetylcholine release is mediated by an A2 adenosine receptor. This is supported by the observations that the excitatory effects of NECA and CGS 21680C were antagonized by PD 115,199.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The shift (4.1) in the concentration-response curve for R-PIA caused by DPCPX (2.5 nM) is consistent with a Ki value for the xanthine of about 0.8 nm, which is of the same order as the Ki value (0.54 nM) obtained for DPCPX in experiments recording nerve-evoked twitch responses from phrenic nerve-diaphragm preparations partially inhibited with tubocurarine and is also of the same order as the K, value for this xanthine at A1 adenosine receptors (Bruns et al, 1987;Lohse et al, 1987 (Hutchison et al, 1989) it seems likely that the excitatory effect of the adenosine analogues on [3H]-acetylcholine release is mediated by an A2 adenosine receptor. This is supported by the observations that the excitatory effects of NECA and CGS 21680C were antagonized by PD 115,199.…”
supporting
confidence: 83%
“…This is supported by the observations that the excitatory effects of NECA and CGS 21680C were antagonized by PD 115,199. Though this xanthine is poorly selective for A2 or A1 adenosine receptors, it is a potent antagonist of the A2 adenosine receptors when the A1 adenosine receptors are blocked by DPCPX (Bruns et al, 1987). Excitatory effects of adenosine analogues on acetylcholine release, probably mediated by A2 adenosine receptors were reported recently (Barry, 1990;Brown et al, 1990).…”
mentioning
confidence: 92%
“…PD1 15199 however shows little selectivity for A2a relative to Al receptors (2.4 fold, Bruns et al, 1987b). ZM 241385 had no additional pharmacological effects at concentrations which blocked A2a adenosine receptors.…”
Section: Discussionmentioning
confidence: 96%
“…The xanthine, PD1 15199 (1,3 dipropyl-8-N-[2-dimethylamino) ethyl]-N-methyl-4-2, 3,6, 7-tetrahydro-2,6-dioxo) -benzenesulphonamidexanthine), although having higher affinity for the A2a binding site than the A2b binding site, is equipotent at A2a and A1 binding sites (Bruns et al, 1987b). PD1 16948 (8-cyclopentyl-1-3-dipropylxanthine) has higher affinity for the A1 receptor than for A2a binding sites in rat brain studies (Bruns et al, 1987a,b;Jarvis et al, 1989) and clearly demonstrated A1-selective antagonism in guinea-pig isolated tissues (Collis et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…CGS21680 (Hutchison et al, , 1990Jarvis et al, 1989) and an iodinatable functionalized congener related to it, PAPA-APEC (Barrington et al, 1989;Jacobson et al, 1989c), are high affinity agonist radioligands that are selective for A 2 -receptors. There are only two reports of adenosine antagonists, namely XAC and PD115,199, as radioligands at A 2 -adenosine receptors (Ukena et al, 1986a;Bruns et al, 1987). Both XAC and PD115,199 bind to A 2 -receptors under the proper circumstances, but neither ligand is A 2 -selective.…”
Section: Discussionmentioning
confidence: 99%